2021
DOI: 10.5194/acp-21-16631-2021
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Molecular characteristics of cloud water in southern China and insights into aqueous-phase processes from Fourier transform ion cyclotron resonance mass spectrometry

Abstract: Abstract. Characterizing the molecular composition of cloud water could provide unique insights into aqueous chemistry. Field measurements were conducted at Mt. Tianjing in southern China in May, 2018. There are thousands of formulas (C5–30H4–55O1–15N0–2S0–2) identified in cloud water by Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). CHON formulas (formulas containing C, H, O, and N elements; the same is true for CHO and CHOS) represent the dominant component (43.6 %–65.3 % of relativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 93 publications
3
15
0
Order By: Relevance
“…Methacrolein (MACR), an important SOA precursor, can be oxidized to produce methacryloyperoxynitrate (MPAN) and methacrylic acid epoxide (MAE) in the gas phase. , MAE can be absorbed by acidic aerosols and subsequently react with H + , SO 4 2 , and NO 3 – to form 2-methylglyceric acid (2-MG), 2-MG-organosulfate, and 2-MG-organonitrate whose characteristic mass spectral fragments were not measured by AMS. Here, we show that the above three products from MAE aqueous reactions were likely formed according to the following: (1) Cloud droplets at this site are acidic . (2) The O:C and H:C in the van Krevelen diagram correspond to the numbers of C and functional groups (>CO) in the three products.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Methacrolein (MACR), an important SOA precursor, can be oxidized to produce methacryloyperoxynitrate (MPAN) and methacrylic acid epoxide (MAE) in the gas phase. , MAE can be absorbed by acidic aerosols and subsequently react with H + , SO 4 2 , and NO 3 – to form 2-methylglyceric acid (2-MG), 2-MG-organosulfate, and 2-MG-organonitrate whose characteristic mass spectral fragments were not measured by AMS. Here, we show that the above three products from MAE aqueous reactions were likely formed according to the following: (1) Cloud droplets at this site are acidic . (2) The O:C and H:C in the van Krevelen diagram correspond to the numbers of C and functional groups (>CO) in the three products.…”
Section: Resultsmentioning
confidence: 90%
“…Nighttime •OH radicals can be recycled from the oxidation of BVOCs with oxidants (e.g., NO 3 • and O 3 ). The isoprene concentration remains high in the early evening which can then react with O 3 and NO 3 • to reproduce •OH to further oxidize LO-OOA to MO-OOA. , Alternatively, the dissolved O 3 in cloud droplets may react with O 2 – to form •OH under acidic conditions via reaction: O 2 – + O 3 + H + → •OH + O 2 . A considerable amount of •OH radicals may exist in the cloud droplets with an average pH of 4.2 reported at this mountain site . The •OH radical in the aqueous phase may be produced via the Fenton reaction (Fe 2+ + H 2 O 2 → Fe 3+ + OH – + •OH, Fe 2+ + ROOH → Fe 3+ + RO – + •OH, and/or Fe 2+ + O 3 +H 2 O → Fe 3+ + O 2 + OH – + •OH) as Fe-containing particles were also found in the cloud residuals at this site. , Moreover, •OH can oxidize LO-OOA to MO-OOA in both the gas and aqueous phases, and a detailed discussion follows for the oxidation pathways of specific BVOCs (i.e., isoprene) in the next section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, cloud water samples with high probability of smoke influence showed significantly higher concentrations compared to samples with a low probability of smoke influence for K + , SO 4 2− , NH 4 + , and TOC, all of which have been previously identified in cloud water influenced by biomass burning events (Budhavant et al., 2014 ; Stahl et al., 2021 ). Previous wildfire influenced cloud water studies have suggested that the TOC composition may contain carbonyls, carboxylic acids, nitrogen‐containing compounds, oligomeric species, and light absorbing secondary organic aerosols formed within clouds (Cook et al., 2017 ; Li et al., 2020 ; Schurman et al., 2018 ; Sun et al., 2021 ; Tomaz et al., 2018 ). These results suggest long‐range transported smoke frequently alters the chemical composition of cloud water at Whiteface Mountain.…”
Section: Discussionmentioning
confidence: 99%
“…Within cloud droplets, aqueous reactions can occur and alter cloud droplet chemical composition (Blando & Turpin, 2000 ; Ervens et al., 2011 ; Sun et al., 2021 ). For example, components of biomass burning aerosols (e.g., levoglucosan, catechol, aminophenol) can react with aqueous hydroxyl radicals to form cloud processing tracers, such as oxalate, malonate, and mesoxalate (Tomaz et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%